Isolation of endophytic fungi with antimicrobial activity from medicinal plant Rhodomyrtus tomentosa (Aiton) Hassk - Dian Handayani, Hanif Hafiza, Rustini Rustini, Purnawan Pontana Putra, Nova Syafni (Journal of Applied Pharmaceutical Science, 2023)
Medicinal plants are an abundant source of natural substances used to treat various diseases; thus, they serve as the foundation for new drug discovery. The interaction between endophytic microorganisms and host plants has been extensively studied because they can produce a wide range of secondary metabolites, including those with significant biological functions from their hosts. This study aimed to isolate the endophytic fungi from the roots, barks, and leaves of the rose myrtle (Rhodomyrtus tomentosa (Ait) Hassk) plant. Endophytic fungi were isolated by direct planting and pour methods. From this plant, 13 endophytic fungi were obtained. Each fungus was grown for 3–4 weeks on rice media. Ethyl acetate was used to extract secondary metabolites from the cultivation results. The antimicrobial activity screening of the extracts was done using the disk diffusion method against microbial pathogens Staphylococcus aureus, Escherichia coli, and Candida albicans. The results showed that three fungus extracts, RTKB3, RTKB4, and RTKB7, had antimicrobial activity against S. aureus and E. coli. However, the extracts did not show inhibition toward the growth of C. albicans. These fungal isolates were identified molecularly as Aspergillus heteromorphic, Aspergillus niger, and Paecilomyces subglobosus. In conclusion, the endophytic fungi from R. tomentosa (Aiton) Hassk were potential producers of antibacterial compounds that need to be investigated further.
Keywords: Antimicrobial activity, endophytic fungi, internal transcribed spacer (ITS), Aspergillus hete